1990
DOI: 10.1111/j.1365-2141.1990.tb06367.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of chromosome abnormalities with laboratory features and clinical course in B‐cell chronic lymphocytic leukaemia

Abstract: 141 patients with B-cell chronic lymphocytic leukaemia (B-CLL) have been studied for a minimum of 12 months and a maximum of 25 years. 30 of 133 patients (32.5%) had greater than 10% FMC7 positive peripheral blood lymphocytes and 19 of 131 patients (14.5%) had a serum or urinary paraprotein. At presentation 88 patients were stage A0, 18 A1, 18 A2, 11 B and six C. 44 (31%) had progressive disease and 42 (30%) died during the study period. 63 patients had a normal karyotype, 75 a clonal abnormality and in three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
1
3

Year Published

1994
1994
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 10 publications
2
39
1
3
Order By: Relevance
“…5,15,13 An association was found between 6qÀ and a high white blood cell (WBC) count, more extensive adenopathy at presentation 15 and shorter treatment-free interval (TFI). 18 The latter finding, however, was not confirmed in another study, 16 showing no difference in terms of clinical behavior between CLL with and without 6qÀ.…”
Section: Introductionmentioning
confidence: 42%
See 1 more Smart Citation
“…5,15,13 An association was found between 6qÀ and a high white blood cell (WBC) count, more extensive adenopathy at presentation 15 and shorter treatment-free interval (TFI). 18 The latter finding, however, was not confirmed in another study, 16 showing no difference in terms of clinical behavior between CLL with and without 6qÀ.…”
Section: Introductionmentioning
confidence: 42%
“…When comparing the 6qÀ group with other CLL cases, a significant difference was only found in the initial WBC count and in the frequency of atypical morphology, as suggested previously. 16,18 In addition, we were able to document an association between CD38 positivity and 6qÀ in 117 assessable cases.…”
Section: The 6qà Is Associated With Intermediate Prognosismentioning
confidence: 80%
“…Whang-Peng et al 11 found an association between 6q deletions and shorter survival in NHL without the translocation t(14;18). Oscier et al 12 in their single center chromosome banding analysis found a shorter treatment-free survival for B-CLL patients with abnormalities involving 6q. However, in the large multicenter banding study compiled by the IWCCLL no adverse prognostic effect of 6q deletions was found.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In several studies, the presence of trisomy 12 has been shown to be associated with a more aggressive clinical course. 1,[3][4][5] The role of genes potentially involved in the pathogenesis of CLL with trisomy 12 is not established. While the critical region of most aberrations in CLL could be narrowed down to a set of candidate genes, this has been difficult in the case of trisomy 12.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies indicated that the bands 12q13-q15 comprise the minimally gained region. 3,[6][7][8] Recent RNA expression analyses showed an overexpression of genes located to chromosome 12 in CLL cases with trisomy 12 as compared to cases without this aberration. 9,10 The aim of the current study was to characterize the protein expression patterns of chromosome 12 candidate genes with oncogenic potential or functional relevance in apoptosis, cell cycle, signal transduction or somatic hypermutation (for details see Table 1) when comparing CLL cases with or without trisomy 12, CD19 þ -Bcells from healthy donors and lymphoma cell lines (JVM-2, EHEB and JURKAT).…”
Section: Introductionmentioning
confidence: 99%